Diagnosis Related Payment for Inpatient Mental Health Care: Hospital Selection and Effects on Length of Stay - Tauchmann, Harald; Reif, Simon; Valder, Franziska (Health Economics, 2025)
We study a policy introducing diagnosis related payment for inpatient mental health care in Germany with rates decreasing over length of stay. Using data on all hospital cases, we first examine which hospitals voluntarily opt into the new scheme. We show that specialized hospitals that treat more complicated cases and are reimbursed more highly under the new scheme select into it. Second, we study the effect of diagnosis related payment on length of stay. We find that diagnosis related payment is associated with large reductions in length of stay but has no effect on mortality, post-acute care, or the ambulatory sector. We argue that the reductions in length of stay are driven by the fact that diagnoses related reimbursement is higher for more complex cases and by payment decreasing over length of stay. This novel evidence contributes to a scarce literature on the role of payment systems for inpatient mental health care and provides important insights for policymakers
Keywords: Mental health care; Provider payment; Policy evaluation; DiD